Perceived risk, fear of Covid-19, and resilience on mental health of Malaysian emerging adults during the Covid-19 pandemic - Keet, Liew Erika Wye; Jen, Low Esther Mei; Lin, Ho Glory Lee; Ting, T'ng Soo; Ho, Khee Hoong (Universitas Negeri Padang, 2021)
The coronavirus (COVID-19) pandemic affects one’s physical and mental state. Past studies reported higher levels of anxiety, distress, and depression, especially among emerging adults, indicating the need of studying how COVID-19 affects one mentally. Hence, this study looked to investigate the predictive effect of perceived risk, fear of COVID-19, and resilience on mental health among Malaysian emerging adults. 182 emerging adults were recruited in the cross-sectional study through an online survey using the purposive sampling method. Results showed that resilience significantly and positively predicted mental health while perceived risk and fear of COVID-19 were insignificant predictors of mental health. Overall, practitioners and policymakers are encouraged to focus on resilience-based interventions to improve our emerging adults' mental health. This is because emerging adults with strong mental health can serve as a strong impetus for national development.